Perioperative Impact of Early Limited Surgical Intervention to Treat Pilon Fractures. (August 2022) - Hreha, Jeremy; Metrione, Michael D.; Reilly, Mark C.; Sirkin, Michael S.; Adams, Mark R.
Background: The operative treatment of pilon fractures is classically treated with a staged protocol with ankle spanning external fixator, followed by definitive open reduction and internal fixation in order to decrease risk of soft tissue complications and infection. However, treatment of pilon fractures with patrial tibial fixation in addition to ankle spanning external fixation at the time of index procedure may facilitate final fixation while avoiding complications that were associated with acute definitive fixation. Methods: Retrospective cohort series of 113 patients treated for pilon fractures from September 2012 to November 2018 at a single level 1 trauma center. Charts were reviewed to compare patients who underwent traditional management with a staged protocol and those who had a limited tibial reduction and fixation (LTRF) during the index procedure. The main outcome measurement was time to definitive fixation. Results: Twenty-six percent of patients (29 of 113) had limited tibial reduction and fixation (LTRF) during index surgery. Mean time between index procedure and definitive ORIF was 4.75 days less for LTRF cohort compared to standard stage cohort (10.86 ± 7.44 vs. 15.61 ± 8.59 days, P = .009). The index procedure took on average 51 minutes longer in the LTRF cohort ( P < .001), yet definitive procedure operative time was decreased by an average of 98 minutes ( P < .001), and overall (index plus definitive) operative duration was shortened by an average of 50 minutes ( P = .044). There was no difference in rate of infection between LTRF (3.1%) and traditional treatment (2.5%) ( P = .86) or reduction quality ( P = .270). There were no nonunions in either treatment group. Conclusion: Patients who had LTRF had quicker time to definitive ORIF and decreased operative time for definitive ORIF. There was no difference in infection rate, reduction quality, or nonunion rate between groups. Level of Evidence: Level IV, Retrospective Cohort Study.